2019
DOI: 10.3390/nu11061302
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Treatment of Sarcopenic Obesity in Women

Abstract: Sarcopenic obesity (SO) is referred to as the combination of obesity with low skeletal muscle mass and function. However, its definition and diagnosis is debated. SO represents a sizable risk factor for the development of disability, possibly with a worse prognosis in women. The present narrative review summarizes the current evidence on pharmacological, nutrition and exercise strategies on the prevention and/or treatment of SO in middle-aged and older-aged women. A literature search was carried out in Medline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 75 publications
2
42
0
3
Order By: Relevance
“…In contrast, chronic caloric restriction might increase muscle protein synthesis rather than downregulate ( 144 , 145 ). Major RCTs in non-sarcopenic women with obesity have suggested that caloric restriction (500 kcal deficit) with at least 0.8 g/kg of protein intake can effectively lose fat and improve physical function ( 146 , 147 ). Moreover, another study has demonstrated that even caloric restriction might cause loss of muscle mass, and hence, it is still more beneficial to mobility and strength when accompanying with resistance training ( 148 ).…”
Section: Treatments For Sarcopenic Obesity and Diabetesmentioning
confidence: 99%
“…In contrast, chronic caloric restriction might increase muscle protein synthesis rather than downregulate ( 144 , 145 ). Major RCTs in non-sarcopenic women with obesity have suggested that caloric restriction (500 kcal deficit) with at least 0.8 g/kg of protein intake can effectively lose fat and improve physical function ( 146 , 147 ). Moreover, another study has demonstrated that even caloric restriction might cause loss of muscle mass, and hence, it is still more beneficial to mobility and strength when accompanying with resistance training ( 148 ).…”
Section: Treatments For Sarcopenic Obesity and Diabetesmentioning
confidence: 99%
“…Sarcopenic obesity has been also associated with an increased risks of functional disability, falls, fractures, cardiovascular diseases, and metabolic disorders [6,[8][9][10][11][12]. The pathogenesis of sarcopenic obesity is multifactorial, encompassing neurological, hormonal, environmental, genetic, and nutritional factors, and their interplay [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…This finding has been contradicted in a study where falls were best predicted by sarcopenia and lean muscle mass [40]. In the setting of sarcopenic obesity, a combination of obesity with low skeletal muscle mass and correction of vitamin D deficiency had a positive role on muscle mass [41].…”
Section: Discussionmentioning
confidence: 95%